2017
DOI: 10.1155/2017/4041768
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is a Protective Response to the Oxidative Damage to Endplate Chondrocytes in Intervertebral Disc: Implications for the Treatment of Degenerative Lumbar Disc

Abstract: Low back pain (LBP) is the leading cause of disability in the elderly. Intervertebral disc degeneration (IDD) was considered as the main cause for LBP. Degeneration of cartilaginous endplate was a crucial harmful factor during the initiation and development of IDD. Oxidative stress was implicated in IDD. However, the underlying molecular mechanism for the degeneration of cartilaginous endplate remains elusive. Herein, we found that oxidative stress could induce apoptosis and autophagy in endplate chondrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Autophagy is a process used to degrade useless proteins or organelles to maintain cellular functions (41). Increasing evidence has indicated that moderate autophagy exhibits a protective function against cellular pathologies, including IDD (42). In addition, a specific study revealed that autophagy-associated genes were downregulated in IDD tissues compared with healthy tissues, including Beclin-1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a process used to degrade useless proteins or organelles to maintain cellular functions (41). Increasing evidence has indicated that moderate autophagy exhibits a protective function against cellular pathologies, including IDD (42). In addition, a specific study revealed that autophagy-associated genes were downregulated in IDD tissues compared with healthy tissues, including Beclin-1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been shown to have a positive effect on cell survival by mediating the selective removal of damaged cell components [54,67]. In addition, autophagy has been shown to instigate a protective effect against oxidative damage to endplate chondrocytes in intervertebral discs as the inhibition of autophagy increased apoptosis [68]. Corresponding with our results, glucosamine was found to activate autophagy in NP cells in a dose-dependent manner and attenuated the decrease of aggrecan to prevent the apoptosis of NP cells induced by IL-1β, whereas 3-MA partly reversed these effects [69].…”
Section: Discussionmentioning
confidence: 99%
“…DLD is often associated with inflammatory status 9 and oxidative stresses. 10 AOS may be beneficial for preventing DLD progression. 11,12 Nanotechnology has provided the possibility of delivering drugs to target tissues via nanoparticles.…”
mentioning
confidence: 99%